2013
DOI: 10.1097/gme.0b013e3182a66aa7
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose paroxetine 7.5 mg for menopausal vasomotor symptoms

Abstract: Paroxetine 7.5 mg is well-tolerated, is effective in reducing the frequency and severity of menopausal vasomotor symptoms, and demonstrates persistence of treatment benefit through 24 weeks of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
131
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 23 publications
4
131
1
Order By: Relevance
“…7,9 However, eligibility criteria in previous trials varied widely and doses of ET differed, precluding direct comparison. In contrast to previous ET trial eligibility criteria of 7+ moderate-to-severe VMS/day, 6,22,23 we required fewer VMS (2+/day) and not all VMS were required to be moderate or severe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,9 However, eligibility criteria in previous trials varied widely and doses of ET differed, precluding direct comparison. In contrast to previous ET trial eligibility criteria of 7+ moderate-to-severe VMS/day, 6,22,23 we required fewer VMS (2+/day) and not all VMS were required to be moderate or severe.…”
Section: Discussionmentioning
confidence: 99%
“…Many SSRI/SNRI have been shown to be more effective than placebo in reducing VMS, 79 with one SSRI recently FDA-approved to treat VMS. 3,9 The SNRI venlafaxine is one of the most widely studied serotonergic agents with accumulating evidence showing that low doses (75–150 mg/day) reduce VMS more than placebo. 1012 SSRI/SNRI are used widely to treat VMS, with venlafaxine a first-line treatment in women unable or unwilling to take ET.…”
Section: Introductionmentioning
confidence: 99%
“…Methodologies for the 12-week and 24-week studies, including participant inclusion and exclusion criteria, study designs, primary efficacy endpoints, and statistical analyses, have been previously described in detail 17. Both studies were conducted in postmenopausal women with moderate to severe VMS associated with menopause.…”
Section: Methodsmentioning
confidence: 99%
“…Brisdelle (paroxetine 7.5 mg; previously called low-dose mesylate salt of paroxetine) is the first and only US Food and Drug Administration–approved nonhormonal option for the treatment of moderate to severe VMS associated with menopause. Two phase 3 studies (ClinicalTrials.gov identifiers NCT01361308 and NCT01101841) demonstrated that paroxetine 7.5 mg reduced moderate to severe VMS in postmenopausal women and was well tolerated 17. Using pooled data from the two phase 3 studies, we examined whether treatment with paroxetine 7.5 mg affected weight, sexual function, or both.…”
mentioning
confidence: 99%
“…Increased testing of non-hormonal treatments for vasomotor symptoms (36) has followed the publication of WHI results, and the FDA recently approved one selective serotonin reuptake inhibitor for vasomotor symptom treatment (6, 7). …”
Section: Introductionmentioning
confidence: 99%